ACHIEVEMENTS OF THE NEW UZBEKISTAN IN POLITICAL, ECONOMIC AND SOCIAL SPHERES.DEVELOPMENT STRATEGIES - Teshaboyeva Nafisa Zubaydulla qizi; Juraboyeva Iroda Qahramon qizi (Ta'lim innovatsiyasi va integratsiyasi, 2024)
Annotation: This annotation provides a summary of the key points regarding Uzbekistan's current development strategies and the significant achievements of Uzbekistan across the political, social, and economic spheres.